Spiritual Care in Nursing Students: Qualitative Study - Claudia Consuelo Torres-Contreras; Lina María Vargas-Escobar; Jorge Yecid Triana-Rodríguez (MedUNAB, 2022)
Introduction. Attention to the spiritual dimension of patients and families is fundamental as part of the active role of nursing professionals in satisfying the spiritual needs of patients. Objective. To understand the attitudes towards spiritual care of nursing professionals in training. Methodology. Qualitative study with content analysis, with a population of 20 higher education Nursing students, with convenience sampling. Semi-structured interviews and two focus groups were held to explore spiritual self-knowledge and the conceptions of spiritual care, using the theoretical concepts proposed by McSherry as a reference. Data was initially analyzed inductively, with help from the Iramuteq software. Results. Spirituality is considered an intrapersonal dimension in which the need to explore one’s own spirituality in recognized, in order to approach the spiritual perception of the patient. Learning about crises for the development of a personal spirituality and finding oneself through nature were part of the observed categories. Discussion. The conception of spiritual care as an intrapersonal dimension helps students differentiate between spirituality and religion. This aspecto has been observable during educational practice, since there were some very religious people and others who were not. Conclusions. Reference is made to the relationship between that which is spiritual and corporeal, and though there is a difference between spirituality and religion, both concepts must be assessed personally. Introducción. La atención de la dimensión espiritual en pacientes y familias es fundamental como parte del papel activo de los profesionales de enfermería en la satisfacción de las necesidades espirituales de los pacientes. Objetivo. Comprender las actitudes frente al cuidado espiritual de los profesionales de enfermería en formación. Metodología. Estudio de abordaje cualitativo, con análisis de contenido, con población de 20 estudiantes de educación superior de Enfermería, con un muestreo por conveniencia. Se realizaron entrevistas semiestructuradas y dos grupos focales para indagar sobre el autoconocimiento espiritual y las concepciones del cuidado espiritual, tomando como referencia los conceptos teóricos propuestos por McSherry. El análisis de los datos inicialmente se hizo de forma inductiva, con ayuda del software Iramuteq. Resultados. La espiritualidad se considera una dimensión intrapersonal donde se reconoce la necesidad de explorar su propia espiritualidad para acercarse a la percepción espiritual del paciente. Aprender de las crisis para el desarrollo de la espiritualidad personal y encontrarse desde la naturaleza fueron parte de las categorías encontradas. Discusión. La concepción del cuidado espiritual para los estudiantes como dimensión intrapersonal, les permite distinguir entre la espiritualidad y la religiosidad. Este es un aspecto que se ha podido ver durante el desarrollo de las prácticas formativas, ya que se han encontrado personas muy religiosas, así como otras que no lo son. Conclusiones. Se hace referencia a la relación entre lo espiritual y lo corpóreo y aunque existe una diferencia entre religión y espiritualidad, los dos conceptos deben ser valorados a nivel personal. Introdução. A atenção à dimensão espiritual em pacientes e familiares é essencial como parte do papel ativo dos profissionais de enfermagem no atendimento às necessidades espirituais dos pacientes. Objetivo. Compreender as atitudes em relação aos cuidados espirituais dos profissionais de enfermagem em formação. Metodologia. Estudo de abordagem qualitativa, com análise de conteúdo, com uma população de 20 estudantes do ensino superior de Enfermagem, com amostragem por conveniência. Foram realizadas entrevistas semiestruturadas e dois grupos focais para indagar sobre autoconhecimento espiritual e concepções de cuidado espiritual, tomando como referência os conceitos teóricos propostos por McSherry. A análise dos dados foi feita inicialmente de forma indutiva, com o auxílio do software Iramuteq. Resultados. A espiritualidade é considerada uma dimensão intrapessoal onde se reconhece a necessidade de explorar a própria espiritualidade para se aproximar da percepção espiritual do paciente. Aprender com as crises para o desenvolvimento da espiritualidade pessoal e encontrar-se com a natureza foram algumas das categorias encontradas. Discussão. A concepção de cuidado espiritual para os alunos como uma dimensão intrapessoal, permite-lhes distinguir entre espiritualidade e religiosidade. Este é um aspecto que se tem visto ao longo do desenvolvimento das práticas formativas, uma vez que foram encontradas pessoas muito religiosas e outras não. Conclusões. É feita referência à relação entre o espiritual e o corpóreo e, embora haja uma diferença entre religião e espiritualidade, os dois conceitos devem ser valorizados a nível pessoal.